Remarks on the genesis and development of ‘shadow elites’ in a comparative context (Economic and Political Thought, 2015)
The article provides a comparative analysis of the anthropologicalconcept of the ‘shadow elites’, which has been introduced by a renownedanthropologists, Janine R. Wedel in her book published in 2009. The ‘shadowelites’ are informal, flexible networks that are formed on the intersectionof business, government, media and science. Moreover, the developmentof shadow elites is characteristic of societies in relatively developed statesand cannot be described simply as corruption or clientelism. In her bookWedel focuses on three examples: the Chubais clan in Russia, the OrdynackaAssociation in Poland and the Richard Perle neoconservative network inWashington. The author of this article accepts Wedel’s definition but arguesthat we still lack a comprehensive theory concerning the genesis of thoseelites. The author strives to propose such a theory and recommends furtherresearch. The author’s concept examines the global processes that disturbthe balance between the three branches of powers in modern states. It isthe author’s contention that the contemporary global political environmentfavors strong executives with little checks from other branches. The informalnetworks circling around the modern executives are, in turn, what constitutesthe shadow elites. The process is observed world-wide, however, thepathologies typically found in post-communist states facilitate it. The authorfocuses especially on the cases related to the UE and Poland. The articleamong other examples describes the connections of the former Polish primeministerKazimierz Marcinkiewicz and the networks of some the personsinvolved in the 2014 Polish wiretapping scandal.